Chylous Ascites: A Rare Adverse Effect of Methimazole Treatment for Grave’s Disease—A Case Report and Review of the Literature - Tawfik Khoury; Ronen Schneider (Case Reports in Endocrinology)
A 40-year-old woman was admitted due to an urticarial rash that was attributed to recent onset of methimazole treatment for a diagnosis of Grave’s disease. The patient had no prior significant medical history and used no medications, including over-the-counter or herbal medications. Her sister had Grave’s disease. On admission, the patient received corticosteroids with improvement in her rash. On the second day of the hospitalization, the patient complained of abdominal discomfort. Abdominal ultrasound revealed a large amount of new onset ascites. Peritoneal tap yielded a milky fluid with high triglyceride level (12.2 mmol/L or 1080 mg/dL), consistent with chylous ascites. After discontinuation of the methimazole, the ascites disappeared. The patient later underwent therapeutic thyroidectomy, after which all features of thyrotoxicosis had improved.